Tourismpreneurship: Local Wisdom-Based Innovation And Market Expansion For Silver Jewelry In Bali - Sang Ayu Putu Shinta Setia Dewi; Bagus Putu Wahyu Nirmala; Putu Wibby Prasetya (Politeknik Internasional Bali, 2026)
The creative economy industry, particularly the craft and fashion sectors, continues to show positive growth in Bali as a world tourism center. This study aims to analyze product development strategies and market expansion of silver jewelry SMEs facing global challenges and digital disruption. The object of this research is Atma Silver Jewelry, which innovated through the